Sosialisasi Strategi Branding Produk Untuk IMK Binaan PDNA Kabupaten Sorong - Ginanjar Abdurrahman; Amalina Maryam Zakiyyah; Reni Umilasari; Sahiruddin Sahiruddin (Journal of Community Development, 2022)
Corona Virus Disease (Covid-19) began to enter Indonesia in March 2020. The spread of this virus was massive in July with the highest case on July 15, 2021. So far, cases have started to decline because the discipline of health protocols has begun to be applied, and most Indonesians have received the Covid-19 vaccine. The growth of Covid-19 had a major impact and became an obstacle to Indonesia's economic growth, especially the Micro and Small Industry (MSI). According to the Asian Development Bank (ADB) there are 50% of Small and Medium Industries went bankrupt due to Covid-19 because turnover has decreased by 40% - 70%. In the Covid-19 pandemic situation, Product Branding can be offered to MSI as one of the solutions to problems to achieve economic resilience. The Community Partnership Program is expected to be able to contribute to solving the problems faced by IMK in Sorong, namely "competitor constraints" and "marketing constraints". In relation to competitor constraints and marketing constraints, MSI is expected to be able to market products easily and be able to compete. For this reason, product branding insight is needed. In this case, MSI actors need to be equipped with product branding insights, so that they can sell their products easily, precisely in booking, easy to recognize their products, and customer loyalty. For this reason, product branding skills need to be socialized to improve the quality of MSI Actors' Human Resources. Based on evaluation results, in general the initial knowledge related to product branding is good, with the lowest score for the pretest 54 and the highest score being 70. Meanwhile, in the posttest score there was a significant increase in the value, with the lowest score being 73 and the highest score reaching 95.